EVALUASI KOMPONEN FISIK BANGUNAN PASAR SAYUR DAN BUAH PEUNAYONG KOTA BANDA ACEH TERHADAP UPAYA RELOKASI - Effan Fahrizal; Teuku Budi Aulia; Safwan Safwan (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Peunayong area is a trade and service area, as well as a heritage tourist area located in Kuta Alam Subdistrict, Banda Aceh City. Since it was inaugurated in 2007 until now Peunayong Vegetable and Fruit Market is not working properly. Traders only want to sell on the first floor, and along the corridor of RA road. Kartini, while the second and third floors are not occupied. In addressing the issue, the Banda Aceh City Government seeks to relocate the Peunayong Market to an integrated market in Lampulo, which is currently under construction. This study aims to identify the factors that cause traders not to occupy the market building of Peunayong Vegetables and Fruits, to identify buyers' perceptions of relocation of Peunayong Vegetable and Fruit Market, and to evaluate the physical, non-physical, and Peunayong Vegetables Market. This research uses qualitative method through observation and interview, and quantitative method through questionnaires distribution. Respondents in this research are 70 traders, and 100 buyers. The results showed that the factors that caused the traders did not occupy the Peunayong Vegetable and Fruit Market building were the buyers did not want to rise to the 2nd floor, the lack of good accessibility for traders and buyers, the constraints of goods circulation, and the number of kiosks and stalls not enough to accommodate all traders. The buyer's perception of the market relocation effort of Vegetables and Peunayong Fruits is built a new market building that can accommodate all traders, have complete public facilities, and designs that follow SOP Kemendag. Evaluation of Peunayong Vegetable and Fruit Market building on the physical component, generally not in accordance with the prevailing regulation with 36.84% level of conformity